Adaptive dynamics of extrachromosomal circular DNA in rice under nutrient stress - Hanfang Ni; Lenin Yong-Villalobos; Mian Gu; Damar Lizbeth López-Arredondo; Min Chen; Liyan Geng; Guohua Xu; Luis Rafael Herrera-Estrella (Nature Communications)
Abstract Extrachromosomal circular DNAs (eccDNAs) have been identified in various eukaryotic organisms and are known to play crucial roles in genomic plasticity. However, in crop plants, the role of eccDNAs in responses to environmental cues, particularly nutritional stresses, remains unexplored. Rice (Oryza sativa ssp. japonica), a vital crop for over half the world’s population and an excellent model plant for genomic studies, faces numerous environmental challenges during growth. Therefore, we conduct comprehensive studies investigating the distribution, sequence, and potential responses of rice eccDNAs to nutritional stresses. We describe the changes in the eccDNA landscape at various developmental stages of rice in optimal growth. We also identify eccDNAs overlapping with genes (ecGenes), transposable elements (ecTEs), and full-length repeat units (full-length ecRepeatUnits), whose prevalence responds to nitrogen (N) and phosphorus (P) deficiency. We analyze multiple-fragment eccDNAs and propose a potential TE-mediated homologous recombination mechanism as the origin of rice’s multiple-fragment eccDNAs. We provide evidence for the role of eccDNAs in the rice genome plasticity under nutritional stresses and underscore the significance of their abundance and specificity.